Temporal registration using 3D phase correlation and a maximum likelihood approach in the perceptual evaluation of video quality - Barkowsky, Marcus; Bialkowski, Jens; Bitto, Roland; Kaup, André (2007 IEEE 9Th International Workshop on Multimedia Signal Processing, MMSP 2007, 2007)
The estimation of the video quality is often performed using a full reference approach. One of the most important steps in a video quality measurement algorithm is to find the corresponding frames between the reference and the distorted video sequence. In this paper an algorithm with three steps is proposed. First, an extended version of the phase correlation is used to find candidate images with an arbitrary temporal offset, spatial scaling or spatial shift. Based on the assumption that the spatial scaling and spatial shift does not change during the sequence a set of probable parameters is selected. Finally, a maximum likelihood estimation is applied to select those temporal offsets which support the smoothest playback. A set of video sequences degraded with several distortions which are typical for multimedia scenarios are used to compare the performance to other algorithms. © 2007 IEE